AGAMA DAN HAK MILIK SEBAGAI SPIRIT PERLAWANAN RAKYAT SEMESTA DALAM PERANG DIPONEGORO - Tobroni, Faiq; Amilia, Fatma (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2019)
The causes of the Diponegoro War or the Java War often get a disproportionate reading. Amongs are the assumptions that interpret the war as Diponegoro's struggle to protect his personal interests (land security) or also the presumption that saw the war to establish an Islamic state. This assumption turned out to be very contradictory to the process of the war. In the war that occurred for five years (1825-1830 AD), it turned out that the backbone of the Diponegoro army was ordinary people (not the army of the Ngayogyakarta Palace). This fact suggests that the war was a universal people's defense consisting of several layers of society (santri, jawara, nobility, etc.). This fact undermines the assumption that the cause of war is religious exclusivism and the interests of Diponegoro's personal priperty. By conducting library research through reading the Volume 1-4 of the Diponegoro Chronicle of Manado and other relevant main works, the researcher found that the causes of the war included the struggle to defend the honor of religion and the state which was symbolized in the public interest. The religious aspect is aimed at the spirit of sub-fertilizing religious elements in the form of resistance to tyrannical actions and the practice of immorality. The public interest is addressed by the spirit of struggle for the property right that is transformed into a spirit of resistance to extortion with an offer of prosperity. The land conflict and the demolition of Diponegoro's residence in Tegalrejo became a symbol of the seizure of property rights which had actually been in the form of extortion to the people in the name of taxes. The feeling of the same boat aroused awareness of ordinary people, santri, jawara and Diponegoro supporters to fight together (universal people's struggle). Keywords: Diponegoro War, Religion, Property Rights, Universal People's Struggle.